Lines of force through the contemporary theatrical device in Cordoba (Argentina): Connections between academia and independent theater. (Ágora de Heterodoxias, 2018)
This work accounts for research carried out at independent theaters in the city of Córdoba, and at the Department of Theater, School of Arts, National University of Córdoba. The inquiry aimed at surveying on-stage procedures and techniques, considering them as lines of force which cross through the contemporary theatrical device. It also aimed at establishing connections between academic and independent circles. Interviews were conducted with directors, actors and different theater makers. More than a hundred plays were seen and recorded, both independent productions and final projects from different classes at the Theater Department, School of Arts, National University of Córdoba.. Furthermore, theatrical productions and theoretical approaches by the authors of this paper were also taken into account. The data yielded by this survey was analyzed against the backdrop of relevant theories and philosophy of drama and aesthetics .It is concluded that some of the problems that appear most strongly in the current theatricality is the crisis of the reality-fiction relationship and the question of art about itself. It is noticed that this weak limit between reality and fiction that is perceived in the social dynamics, is assumed by the theater, which in turn erases its own limits, as a critical view on the web of power that constructs reality.
Keywords: contemporary theater; Córdoba; University; independent scene